2021
DOI: 10.1039/d0na01053g
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically rollable photodetectors enabled by centimetre-scale 2D MoS2 layer/TOCN composites

Abstract: Two-dimensional (2D) molybdenum disulfide (MoS2) layers are suitable for visible-to-near infrared photodetection owing to their tunable optical bandgaps. Also, their superior mechanical deformability enabled by extremely small thickness and van...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Figure h shows the UV–visible absorbance spectrum for 2D SnS layers directly grown on a glass substrate along with the corresponding optical microscopy image (inset). Figure i presents the corresponding Tauc plot of (α h ν) 1/2 vs h ν converted from the absorbance spectrum, where α is the optical absorption coefficient and h ν is the photon energy . The extrapolation of the Tauc plot reveals that the optical band gap energy of 2D SnS layers is in a range of ∼1.0–1.1 eV, which agrees well with previous studies. , The semiconducting characteristics of 2D SnS layers were further verified by variable-temperature electrical characterizations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure h shows the UV–visible absorbance spectrum for 2D SnS layers directly grown on a glass substrate along with the corresponding optical microscopy image (inset). Figure i presents the corresponding Tauc plot of (α h ν) 1/2 vs h ν converted from the absorbance spectrum, where α is the optical absorption coefficient and h ν is the photon energy . The extrapolation of the Tauc plot reveals that the optical band gap energy of 2D SnS layers is in a range of ∼1.0–1.1 eV, which agrees well with previous studies. , The semiconducting characteristics of 2D SnS layers were further verified by variable-temperature electrical characterizations.…”
Section: Resultsmentioning
confidence: 99%
“…Wearable electronics that can convert mechanical energy into electrical energy have received increasing attention in a range of technologies, such as healthcare and medical applications. In this regard, two-dimensional (2D) materials offer distinct advantages with their ability to maintain high structural integrity under excessive mechanical stimuli owing to their large strain limits. , Among a variety of atomically thin 2D materials, those with intrinsic piezoelectric properties are considered promising for energy-harvesting applications. Particularly, group IV 2D monochalcogenides (MXs; where M = Sn or Ge and X = S or Se) have received significant attention due to the large in-plane piezoelectricity originating from their van der Waals (vdW) hinge-like layered structure. , While a large family of 2D monochalcogenides has been explored, tin monosulfide (SnS) 2D layers exhibit intriguing properties enabled by their structural anisotropy such as high piezoelectric coefficients as well as ferroelectricity-driven gating and synaptic characteristics . Despite these appealing structure–property aspects, the centimeter-scale chemical synthesis of morphologically homogeneous 2D SnS layers has been limited, hindering their practical applications .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2(a) shows a schematic illustration of the fabrication process of a VA-2D MoS 2 /TOCN gas sensor. The fabrication starts with the wafer-scale CVD growth of the VA-2D MoS 2 layers with a typical lateral dimension of ∼10 cm×2 cm on top of a SiO 2 /Si wafer [15,[45][46][47][48][49]. Mo film of a controlled thickness (∼6 nm) is deposited on a clean SiO 2 /Si wafer via electron beam evaporation followed by the CVD sulfurization reaction, which converts the Mo films into VA-2D MoS 2 layers, as previously demonstrated [18,50,51].…”
Section: Resultsmentioning
confidence: 99%
“…The characterization of the 3D rolled-up device shows that the photocurrent increases linearly to the light intensity, exhibiting good sensitivity. Figure 6(c)-(i) shows that MoS 2 nanomembranes are integrated on an optically transparent substrate to form a rolled-up photodetector [27]. It is demonstrated that the 3D rolled-up photodetector exhibits a faster response time and stability, as shown in figure 6(c)-(ii).…”
Section: Microtubular Photodetectormentioning
confidence: 87%
“…While for the material aspect, semiconductor materials of IV and III-V groups obtain high quality responses to light owing to their intrinsic properties [22][23][24][25]. 2D layered materials such as graphene and MoS 2 are also widely used due to their atomic thickness, flexibility, enhanced light-matter interactions, and the ability to form heterostructures bonded by van der Waals forces [26,27]. 3D assembly techniques based on nanomembranes made from above materials, including rolling, folding, buckling and pick-place methods, have already been used to prepare novel devices for nanophotonics and optoelectronics.…”
Section: Introductionmentioning
confidence: 99%